Digital Capitalism Behind the “Broadcast Yourself” Tagline: (Study of Digital Discourse on the Popularity in Indonesia’s YouTube Content Industry) - Febriyanti, Syafrida Nurrachmi; Ida, Rachmah (Jurnal Komunikasi, 2023)
Through its phenomenal jargon "Broadcast Yourself", YouTube seems to be an important instrument for social life because this platform is designed for amateurs who want to publish their content so that it can be recognized by the whole world. But is it true that this jargon has changed the position of the audience from being just consumers on conventional media to becoming prosumers on the YouTube platform? This research attempts to examine popular content on YouTube in 2018-2020 to obtain an overview of the growing YouTube content industry in Indonesia as well as competition between user-generated content and professional-generated content. ). Digital labor theory from Christian Fuchs is used to read digital capitalism practices that occur on the YouTube platform, while the research methodology used is digital discourse by looking at four dimensions including text, context, action and interaction as well as ideology and power. This research concludes that there has been a practice of digital capitalism on the YouTube platform which can be seen from how the audience has experienced multiple layers of exploitation as free labor on the YouTube platform. Audiences do not only work for capitalist corporations that sell personal data to advertisers, they also become the backbone of capital corporations through the video content they produce. Apart from that, the audience also works for other audiences who are content creators.